Non-secreting pituitary tumours characterised by enhanced expression of YAP/TAZ. Issue 1 (January 2019) - Xekouki, Paraskevi; Lodge, Emily J; Matschke, Jakob; Santambrogio, Alice; Apps, John R; Sharif, Ariane; Jacques, Thomas S; Aylwin, Simon; Prevot, Vincent; Li, Ran; Flitsch, Jörg; Bornstein, Stefan R; et al.
Abstract : Tumours of the anterior pituitary can manifest from all endocrine cell types but the mechanisms for determining their specification are not known. The Hippo kinase cascade is a crucial signalling pathway regulating growth and cell fate in numerous organs. There is mounting evidence implicating this in tumour formation, where it is emerging as an anti-cancer target. We previously demonstrated activity of the Hippo kinase cascade in the mouse pituitary and nuclear association of its effectors YAP/TAZ with SOX2-expressing pituitary stem cells. Here, we sought to investigate whether these components are expressed in the human pituitary and if they are deregulated in human pituitary tumours. Analysis of pathway components by immunofluorescence reveals pathway activity during normal human pituitary development and in the adult gland. Poorly differentiated pituitary tumours (null-cell adenomas, adamantinomatous craniopharyngiomas (ACPs) and papillary craniopharyngiomas (PCPs)), displayed enhanced expression of pathway effectors YAP/TAZ. In contrast, differentiated adenomas displayed lower or absent levels. Knockdown of the kinase-encoding Lats1 in GH3 rat mammosomatotropinoma cells suppressed Prl and Gh promoter activity following an increase in YAP/TAZ levels. In conclusion, we have demonstrated activity of the Hippo kinase cascade in the human pituitary and association of high YAP/TAZ with repression of the differentiated state both in vitro and in vivo . Characterisation of this pathway in pituitary tumours is of potential prognostic value, opening up putative avenues for treatments.